Modeling Light Response of Electron Transport Rate and Its Allocation for Ribulose Biphosphate Carboxylation and Oxygenation - Ye, Zi-Piao; Kang, Hua-Jing; An, Ting; Duan, Hong-Lang; Wang, Fu-Biao; Yang, Xiao-Long; Zhou, Shuang-Xi (Frontiers in Plant Science, 2020)
Accurately describing the light response curve of electron transport rate (J–I curve) and allocation of electron flow for ribulose biphosphate (RuBP) carboxylation (JC–I curve) and that for oxygenation (JO–I curve) is fundamental for modelling of light relations of electron flow at the whole-plant and ecosystem scales. The non-rectangular hyperbolic model (hereafter, NH model) has been widely used to characterize light response of net photosynthesis rate (An; An–I curve) and J–I curve. However, NH model has been reported to overestimate the maximum An (Anmax) and the maximum J (Jmax), largely due to its asymptotic function. Meanwhile, few efforts have been delivered for describing JC–I and JO–I curves. The long-standing challenge on describing An–I and J–I curves haves been resolved by a recently developed An–I and J–I models (hereafter, Ye model), which adopts a nonasymptotic function. To test whether Ye model can resolve the challenge of NH model in reproducing J–I, JC–I and JO–I curves over light-limited, light-saturated and photoinhibitory I levels, we compared the performances of Ye model and NH model against measurements on two C3 crops (Triticum aestivum L. and Glycine max L.) grown in field. The results showed that NH model significantly overestimated the Anmax and Jmax for both species, which can be accurately obtained by Ye model. Furthermore, NH model significantly overestimated the maximum electron flow for carboxylation (JC-max) but not the maximum electron flow for oxygenation (JO-max) for both species, disclosing the reason underlying the long-standing problem of NH model – overestimation of Jmax and Anmax.